PENGARUH PELATIHAN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA HOTEL GRAND INNA KUTA - I Nyoman Andi Sumerta; Dewiwati Sujadi (Universitas Triatma Mulya, 2020)
Competition is facing the era of increasingly high free trade, including competition in the tourism sector. So it requires human resources who have the knowledge and skills that can meet global demands so that a development program is needed to increase the ability to carry out duties and responsibilities. This research aims to analyze the effect of job training and communication on employee performance at the Grand Inna Kuta Hotel. The data collection technique in this research is a questionnaire. Sampling in this research using disproportional sampling method. The respondents who were taken as samples in this research were 108 employees of the Grand Inna Kuta Hotel. The analytical tools used to answer the problems in this research are data quality test, classical assumption test and multiple regression analysis. The results of the analysis resulted in the regression equation model Y = 9,059 + 0.322 X1 + 0.174 X2. Job training has a positive and significant effect of 0.322, confirmed by testing the hypothesis which shows the tcount of 2.305 is greater than the t table of 1.657, with a significance of 0.023 (0.023 <0.05). Communication (X2) has a positive and significant effect on employee performance (Y) of 0.174, confirmed by hypothesis testing which shows that the tcount of 1.969 is greater than the t table of 1.657 with a significance of 0.042 (0.042 <0.05). Job training independent variable (X1) has a standardized coefficients beta value of 0.264, while communication has a standardized coefficients beta value of 0.226, so it can be concluded that job training independent variable (X1) has a more dominant influence on employee performance. Meanwhile, job training and communication together contributed 19.7% to the employee performance of Hotel Grand Inna Kuta.